ANALISIS CONCEPT IMAGE DAN CONCEPT DEFINITION PADA PEMBELAJARAN TEKS REKON SISWA KELAS IX DI SMP NEGERI 36 MAKASSAR - Dina Mutiah; Abdul Haliq; Asis Nojeng (STKIP Subang, 2026)
This study aims to describe: (1) the Concept Image and Concept Definition of ninth-grade students regarding recon texts at SMP Negeri 36 Makassar. (2) the Concept Definition of recon texts as explained by teachers in Indonesian language learning. The results of the study indicate that: (1) the Concept Image and Concept Definition of ninth-grade students regarding recon texts show significant variations. Some students have had a conceptual balance between the intuitive image and the formal definition of recon texts, while others experience conceptual imbalance due to the inconsistency between the inherent Concept Image and the correct Concept Definition, especially in understanding the structure and linguistic characteristics of recon texts; (2) the Concept Definition conveyed by the teacher has systematically covered the meaning, function, structure, and linguistic characteristics of recon texts, but the understanding and internalization of these concepts by students is not evenly distributed even though learning strategies have been implemented such as activating prior experiences and modeling through learning media. Based on the results of the study, it can be concluded that the conflict between Concept Image and Concept Definition is the main cognitive root of student misconceptions, so that more reflective and explicit learning interventions are needed in restructuring students’ intuitive schemes to align with the demands of the formal concept of the curriculum.